Linguistic Colonialism in the English Language Textbooks of Multinational Publishing Houses - Jairo Eduardo Soto-Molina; Pilar Méndez (Asociación Colombiana de Profesores de Ingles, 2020)
The purpose of this paper is to examine and compare the concepts of linguistic colonialism and cultural alienation in University textbooks for teaching English as opposed to the theories about culture in the decolonial turn. Dichotomous categories were established based on the analysis of the cultural component of the textbooks for the teaching of English. The corpus consisted of six textbooks produced by multinational publishers and used in Colombia during the years 2006-2018. Documentary analysis procedures were used to discuss emergent themed contents in relation to cultural components from a critical perspective that unveiled imperialism practices. Results showed that the textbook contents dealt with high levels of alienation burden, superficial cultural components and instrumentation to the submissive person who favors the dominant culture of English and does not offer possibilities to embrace interculturality in ELF teaching contexts.